Enhancing the performance of green solid-state electric double-layer capacitor incorporated with fumed silica nanoparticles - Chong, Mee Yoke; Numan, Arshid; Liew, Chiam-Wen; Ng, H.M.; Ramesh, Kasi; Ramesh, Subramaniam (Elsevier, 2018)
Solid polymer electrolyte (SPE) based on fumed silica nanoparticles as nanofillers, hydroxylethyl cellulose (HEC) as host polymer, magnesium trifluoromethanesulfonate salt and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ionic liquid is prepared by solution casting technique. The ionic conductivity, interactions of adsorbed ions on the host polymer, structural crystallinity and thermal stability are evaluated by electrochemical impedance spectroscopy (EIS), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and thermogravimetric analysis (TGA), respectively. Ionic conductivity studies at room temperature reveals that the SPE with 2 wt. % of fumed silica nanoparticles gives the highest conductivity compared to its counterpart. The XRD and FTIR studies confirm the dissolution of salt, ionic liquid and successful incorporation of fumed silica nanoparticles with host polymer. In order to examine the performance of SPEs, electric double-layer capacitor (EDLC) are fabricated by using activated carbon electrodes. EDLC studies demonstrate that SPE incorporated with 2 wt. % fumed silica nanoparticles gives high specific capacitance (25.0 F/g) at a scan rate of 5 mV/s compared to SPE without fumed silica. Additionally, it is able to withstand 71.3% of capacitance from its initial capacitance value over 1600 cycles at a current density of 0.4 A/g.